The Global Minimum Tax - Niels Johannesen (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2022)
This paper studies how the global minimum tax shapes national tax policies and welfare in a formal model of international tax competition with heterogeneous countries. The net welfare effect is generally ambiguous from the perspective of non-havens. On the one hand, the global minimum tax raises their welfare by curbing profit shifting, which boosts government revenue. One the other hand, it lowers their welfare by increasing equilibrium tax rates in havens, which transfers real resources from non-haven firms to haven governments. The net welfare effect is unambiguously positive when the global minimum rate is so high that profit shifting ends.
Keywords: H25; H26; H77; 330; profit shifting; international taxation; global minimum tax; tax avoidance; multinational firms